Evaluation the Effectiveness of Different Concentrations Phenols, Alkaloids and Terpenes Extracted from Pimpinella anisum against Phytophthora Fungi. - J. Fradi, Ahmed (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2022)
This study did the isolation, purification, and identification of the fungus Phytophthora cinnamomi of some infected plants, including Chili pepper, cucumber, and eggplant. The green parts of Pimpinella anisum plant were grounded to a semi-powdered state. Phenols, alkaloids and terpenes were extracted from this plant, then the anti-fungal activity was evaluated at different concentrations of 5% and 10%. The percentage of radial growth inhibition of fungi with plant extracts was measured after seven days of incubation. The results showed that the terpene extract was the most effective against fungi and the alkaloid extract had the least antifungal activity. the percentage of radial growth inhibition was 97%-65%, respectively.